Peningkatan Hasil Belajar SKI melalui Pendekatan Mind Mapping pada Siswa MTs YAPIMA Depok - Karamatih, Mutiyara Indah; Fikriyah, Fuji Zakiyatul (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2025)
This study aims to determine the effectiveness of the mind mapping approach in improving learning outcomes of Islamic Cultural History (SKI) subjects in grade VII students at MTs Yapima Depok. The method used is classroom action research (CAR) Kemmis Mc.Taggart model which is implemented in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results of the study indicate that the application of mind mapping can improve students' understanding and retention of SKI subject matter. There was a significant increase in the average value of students from pre-cycle to cycle II, as seen in the classical completeness obtained by students in cycle I reaching 64% and in cycle II reaching 100%. In addition, students showed higher enthusiasm and participation during the learning process. Thus, the mind mapping approach is proven to be effective as a learning strategy that can improve SKI learning outcomes at the MTs level.